Natural Convection Flow in Semi-Trapezoidal Porous Enclosure Filled with Alumina-Water Nanofluid Using Tiwari and Das’ Nanofluid Model - VEDAVATHI, Nallapati; VENKATADRI, Kothuru; FAZURUDDIN, Syed; RAJU, G. Sankara Sekhar (Engineering Transactions, 2022)
Nowadays, optimal parameters are necessary for heat transfer enhancement in different practical applications. A numerical simulation of natural convection in a semi-trapezoidal enclosure embedded with porous medium is presented. Stream function and temperature using the Darcy–Boussinesq approximation and Tiwari and Das’ nanofluid model with new more realistic empirical correlations for the physical properties of the nanofluids are formulated. The developed partial differential equations are employed with the help of the stream function approach. The in-house developed computational MATLAB code is validated with the previously published work. The impact of a wide range of governing parameters on fluid flow patterns and temperature gradient variations is presented. The thermal Rayleigh number (Ra) can be a control key parameter for heat and convective flow. Thermal dispersion effects are also examined in this study. An increase in the Rayleigh number leads to an increase in heat transfer, where one can find a reduction of convective heat transfer with Φ.